Facilitators and barriers in anorexia nervosa treatment initiation (FABIANA): study protocol for a mixed-methods and multicentre study. Issue 6 (November 2019) - Kästner, Denise; Buchholz, Ines; Weigel, Angelika; Brunner, Romuald; Voderholzer, Ulrich; Gumz, Antje; Löwe, Bernd
Abstract : Background: Anorexia nervosa is a serious disorder, which often takes a chronic course. Early treatment leads to a significantly better prognosis and prevents chronicity. However, existing evidence on facilitators and barriers in anorexia nervosa treatment initiation is scarce. Aims: Against this background, the FABIANA study (ClinicalTrials.gov Identifier: NCT03713541) aims to (a) identify potentially modifiable facilitators and barriers from the perspectives of adolescent and adult patients with anorexia nervosa, carers and physicians, (b) develop and test an instrument for the combined assessment of multiple key facilitators and barriers, and (c) quantify the effect of potentially modifiable versus non-modifiable key facilitators and barriers on the duration of untreated illness (DUI) in patients with anorexia nervosa. Method: FABIANA is an observational, mixed-method-study divided into three consecutive substudies each corresponding to one of the study aims. All three substudies will include female patients with anorexia nervosa aged 14 years and older at the beginning of their first psychotherapeutic anorexia nervosa treatment. The qualitative substudy I and the quantitative substudy III will additionally include carers and involved physicians. The recruitment will take place at 20 cooperating study centres throughout Germany, which provide in-patient or out-patient anorexia nervosa specialist care. The DUI will be calculated based on the month of illness onset as determined in validated interviews on lifetime anorexia nervosa symptoms and the therapist-reported date of treatment initiation. Conclusions: Strengths and limitations of the retrospective assessment of the DUI will be discussed. The findings of the FABIANA study will contribute to the development of evidence-based early-intervention approaches and the prevention of a chronic course of illness. Trial registration: ClinicalTrials.gov Identifier: NCT03713541. Declaration of interest: None.